2000
DOI: 10.1002/(sici)1097-4652(200003)182:3<323::aid-jcp2>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

T‐cell recognition of melanoma‐associated antigens

Abstract: In this review, we summarize the significant progress that has been made in the identification of melanoma-associated antigens (MAA) recognized by cytotoxic T-lymphocytes (CTL). These antigens belong to three main groups: tumor-associated testis-specific antigens (e.g. , MAGE, BAGE, and GAGE); melanocyte differentiation antigens (e.g., tyrosinase, Melan-A/MART-1); and mutated or aberrantly expressed molecules (e.g, CDK4, MUM-1, beta-catenin). Although strong CTL activity may be induced ex vivo against most of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(42 citation statements)
references
References 56 publications
0
40
0
2
Order By: Relevance
“…Most of these antigens have been cloned from melanoma cells 2 and less frequently from other types of cancer. 3,4 For the development of effective immunotherapy against cancer, the identification of a larger variety of tumor-associated antigens is of great importance, to broaden the range of different tumors that can be treated as well as to prevent the outgrowth of antigen-loss tumor cells after vaccination.…”
mentioning
confidence: 99%
“…Most of these antigens have been cloned from melanoma cells 2 and less frequently from other types of cancer. 3,4 For the development of effective immunotherapy against cancer, the identification of a larger variety of tumor-associated antigens is of great importance, to broaden the range of different tumors that can be treated as well as to prevent the outgrowth of antigen-loss tumor cells after vaccination.…”
mentioning
confidence: 99%
“…This method is based on the detection of antigens within recombinantly expressed tumor cDNA phage libraries by autologous antibodies (21). One variant of the method (22), which has also been applied in the present study, aims directly at the identification of antigens that are expressed solely in tumors and germline cells such as MAGE genes (23,24). Cancer germline genes are expressed only in spermatoids͞spermatogones and in tumors and thus, in view of the fact that the testis is an immunoprivileged site, can be considered immunologically tumorspecific (25,26).…”
mentioning
confidence: 99%
“…Identification of tumor antigens and their optimal antigenic peptides over the past decade opened new approaches to the understanding of melanoma antigenicity and allowed development of peptide-based vaccine strategies. 1 The results of most clinical trials, however, indicated that progress must be made before peptide-based vaccines can be added to the therapeutic arsenal against melanoma. [2][3][4] Many studies demonstrated that immunization with antigenic peptides alone is not sufficient to elicit an efficient cytotoxic T lymphocyte (CTL) response, or even any response at all.…”
Section: Abstract: Melanoma; Cancer; Vaccine; Lipopeptides; Cd8 ϩ T mentioning
confidence: 99%